Addressing the challenges of college health in international education. Issue 4 (19th May 2022) - Ibrahim, Halah; O'Connell, Chris
Abstract: Globalization has become a major force in higher education. Yet, far too little attention has been paid to the effects of the globalization of higher education, whether positive or adverse, on student health. We examine the applicability of the perspectives on the benefits and challenges of globalized healthcare to university student health. Specifically, we question: (1) Do the international healthcare resources adequately meet the needs of adolescents who are living and studying outside their home country? (2) Is a Western framework of medicine being imposed on non-Western cultures? (3) Can student health regulations, best practices, and policies be implemented at an international level? We conclude each section with modest proposals. Our hope is that this article will start the conversation that will expand the research and broaden the perspectives on the globalization of higher education for the benefit of students and the universities and healthcare providers that serve them.